Impact of Service Quality on Customer Satisfaction: A Case Study in Educational Institutions - Herman, Herman (ADPEBI International Journal of Business and Social Science, 2022)
This study aims to determine the effect of service quality on student satisfaction. The sample in this study was 81 people. In analyzing the data obtained from this study, the authors used descriptive analysis and quantitative analysis methods. From the results of research with descriptive analysis, it is stated that the respondents' responses to the service quality variable are agree and the student satisfaction variable is agree. Based on the results of research with quantitative analysis, it is known that the quality of service has a positive and significant effect on student satisfaction. Result by test of determination showed that (R2) is 0.849. Which means that the service quality variable has an influence of 84.9% on student satisfaction. the remaining 15.1% is influenced by variables not examined.